Genetic variability and relative importance of characters in tomato germoplasm accessions - Marim, Bruno Garcia; Silva, Derly José Henriques da; Carneiro, Pedro Crescêncio Souza; Miranda, Glauco Vieira; Mattedi, André Pugnal; Caliman, Fabiano Ricardo Brunele (Pesquisa Agropecuaria Brasileira, 2010)
The objectives of this work were to characterize the genetic diversity of tomato accessions from the Vegetable Germplasm Bank of Universidade Federal de Viçosa (BGH-UFV) and to evaluate the relative importance of characters in determining this diversity. Seventy tomato accessions were evaluated in three experiments in a randomized block design with three replicates, using the Santa Clara and Débora Plus cultivars as controls. In the first experiment (January to July 2002), 30 accessions were evaluated; in the second (August to December 2002) and the third (January to July 2003) experiments, 20 accessions were evaluated. The divergence study was performed through the joint analysis of variance, the grouping of the averages by the Scott-Knott test, and the grouping of accessions by Tocher's method. The study of the relative importance of characters was done by the Singh method and by canonical variables. The variability for 16 characters was verified by the Scott-Knott test, and the accessions were separated in ten groups according to Tocher's method. There is great genetic diversity between tomato accessions of BGH-UFV, with high variation in morphologic, agronomic and quality characteristics.